MOF-based multi-stimuli-responsive supramolecular nanoplatform equipped with macrocycle nanovalves for plant growth regulation. (15th October 2021) - Yang, Jie; Dai, Dihua; Cai, Zhi; Liu, Yu-Qing; Qin, Jian-Chun; Wang, Yan; Yang, Ying-Wei
Abstract: Controllable and on-demand delivery of agrochemicals such as plant hormones is conducive to improving agrochemicals utilization, tackling water and environmental pollution, reducing soil acidification, and realizing the goals of precision agriculture. Herein, a smart plant hormone delivery system based on metal-organic frameworks (MOFs) and supramolecular nanovalves, namely gibberellin (GA)-loaded CLT6@PCN-Q, is constructed through supramolecular host-guest interaction to regulate the growth of dicotyledonous Chinese cabbage and monocotyledonous wheat. The porous nanoscale MOF (NMOF) with a uniform diameter of 97 nm modified by quaternary ammonium (Q) stalks is served as a cargo reservoir, followed by the decoration of carboxylated leaning tower[6]arene (CLT6) based nanovalves on NMOF surfaces through host-guest interactions to fabricate CLT6@PCN-Q with a diameter of ∼101 nm and a zeta potential value of -13.2 mV. Interestingly, the as-fabricated supramolecular nanoplatform exhibits efficient cargo loading and multi-stimuli-responsive release under various external stimuli including pH, temperature, and competitive agent spermine (SPM), which can realize the on-demand release of cargo. In addition, GA-loaded CLT6@PCN-Q is capable of effectively promoting the seeds germination of wheat and stem growth of dicotyledonous Chinese cabbage and monocotyledonous wheat (1.86 and 1.30 times of control groups, respectively). The smart supramolecular nanoplatform based on MOFs and supramolecular nanovalves paves a way for the controlled delivery of plant hormones and other agrochemicals for promoting plant growth, offering new insights and methods to realize precision agriculture. Statement of significance: To achieve controllable and sustainable release of cargos such as agrochemicals, a smart MOF-based multi-stimuli-responsive supramolecular nanoplatform equipped with supramolecular nanovalves was fabricated via the host-guest interaction between quaternary ammonium stalks-functionalized nanoMOFs and water-soluble leaning tower[6]arene. The as-prepared supramolecular nanoplatform with uniform diameter distribution demonstrated good cargo release in response to various external stimuli. The installation of synthetic macrocycles could effectively reduce cargo loss in the pre-treatment process. This type of supramolecular nanoplatform exhibited good promoting effect on seed germination and plant growth dicotyledonous Chinese cabbage and monocotyledonous wheat. As an eco-friendly, controlled, and efficient cargo delivery system, this supramolecular nanoplatform will be a promising candidate in precision agriculture and controlled drug release to attract the broad readership. Graphical abstract: Image, graphical abstract